A Taylor-Made Design of Phenoxyfuranone-Type Strigolactone Mimic - Fukui, Kosuke; Yamagami, Daichi; Ito, Shinsaku; Asami, Tadao (Frontiers in Plant Science, 2017)
Strigolactones are a class of plant hormones that inhibit axillary bud outgrowth and are released from plant roots to act as a rhizosphere communication signal. The Orobanchaceae parasitic plant Striga hermonthica perceives strigolactone as its germination signal, indicating host presence. After germination, the Striga plant parasitises the host plant and suppresses host growth by draining photosynthetic products, water and other essential nutrients. Because of this way of life, this parasite threatens crop production in sub-Saharan Africa with infestation in crop fields and crop devastation. Crop protection in such areas is among the most concerning problems to be dealt with as immediately as possible. With respect to crop protection from Striga, many strigolactone agonists have been developed and used in research to reveal Striga biology, and have contributed to development of crop protection methods. However, an effective method has yet to be found. In a previous study, we reported debranones as a group of strigolactone mimics that inhibit axillary buds outgrowth with moderate stimulation activity for Striga germination. Debranones would be accessible because they are simply synthesised from commercially available phenols and bromobutenolide. Taking this advantage of debranones for Striga research, we tried to find the debranones stimulating Striga seed germination. To modulate functional selectivity and to enhance germination inducing activity of debranones, we studied structure–activity relationships. We investigated effects of substituent position and functional group on debranone activity and selectivity as a strigolactone mimic. As a result, we improved stimulation activity of debranones for Striga seed germination by chemical modification, and demonstrated the pharmacophore of debranones for selective modulation of distinct strigolactone responses.